CUSTOMER DECISIONS TO USE BANK MUAMALAT PRODUCTS AND SERVICES RANTAU PRAPAT BRANCH - Rahman, Dani; Arif, Muhammad; Dalimunthe, Ahmad Amin (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Bank Muamalat Rantau Prapat Branch began operating in 2010 and showed significant growth in 2011 and 2012. In the following years, business development and the number of Bank customers tend to stagnate in 2018, 2019, 2020 and 2021 which can result in a decrease in branch profits and rational efficiencies such as employee layoffs, moving to smaller offices, reducing branch status and others. So research is needed to find out and measure what factors make existing customers want to use products and services at the Rantau Prapat branch office. With these factors known, it can become management policy material for market penetration with the type of products and supporting strategies that are in accordance with known factors so that it is expected that the branch office will grow significantly in the future. The research is only concentrated on the coverage area of Bank Muamalat Rantau Prapat Branch services, namely: North Labuhan Batu, Labuhan Batu, South Labuhan Batu districts, hence the possibility that in other areas the research results will vary with the same variables. The independent variables measured in this study are: Culture, Psychology, Personal, Social and Environment, with Customer Decisions as the dependent variable. The research method uses a positive affirmation Likert scale, multiple linear regression, t test and F test. The results showed that partially cultural, social, personal and environmental factors had no significant effect on customer decisions, while psychological factors had a significant effect on customer decisions. Together and simultaneously five independent variable factors have a very significant effect on customer decisions using Bank Muamalat products and services Rantau Prapat Branch.